Pengamanan File Audio Menggunakan Algoritma Kriptografi Blowfish Dan Pengujian UAT - Siswanto; Farizal Dias Amsari; Basuki Hari Prasetyo; Wahyu Pramusinto; Gunawan Pria Utama; M. Anif (Ikatan Ahli Informatika Indonesia, 2021)
The current problem at PT. Central Asia Insurance is data or information from meeting recordings that have been made without security so that the resulting data is leaked and can be published by unauthorized persons. This study aims to secure the results of the meeting in the form of audio that will be sent to the branch of PT. Central Asia Insurance using blowfish cryptographic algorithm and UAT testing. Therefore, I created an encryption application to secure the audio from the meeting at PT. Central Asia Insurance. The goal is to prevent irresponsible people from being able to know the results of the meeting directly because the Audio file has been encrypted. By making this application, it can guarantee the audio file of the meeting at PT. Central Asia insurance can be accepted by people who are entitled and have keys. The final result of this research is that this application is able to encrypt audio files with a maximum data size of 120 Mb. Based on trials carried out as many as 15 encrypted files, the encrypted file size becomes large with an average value of 12,009,507 bytes and an average encryption process time of 37.0 seconds while the decryption time is 52.2 seconds. So that the files obtained can be protected and can only be accessed by users who have a password lock. In the UAT test, a questionnaire with a Likert scale scale of 5. has been used. As a result, the respondents agree (above 91.23%) that the overall application of the blowfish algorithm to secure data files can be kept confidential.